Targeting ATR in DNA damage response and cancer therapeutics - Fokas, E; Prevo, R; Hammond, E; Brunner, T; McKenna, W; Muschel, R (Elsevier, 2014)
The ataxia telangiectasia and Rad3-related (ATR) plays an important role in maintaining genome integrity during DNA replication through the phosphorylation and activation of Chk1 and regulation of the DNA damage response. Preclinical studies have shown that disruption of ATR pathway can exacerbate the levels of replication stress in oncogene-driven murine tumors to promote cell killing. Additionally, inhibition of ATR can sensitise tumor cells to radiation or chemotherapy. Accumulating evidence suggests that targeting ATR can selectively sensitize cancer cells but not normal cells to DNA damage. Furthermore, in hypoxic conditions, ATR blockade results in overloading replication stress and DNA damage response causing cell death. Despite the attractiveness of ATR inhibition in the treatment of cancer, specific ATR inhibitors have remained elusive. In the last two years however, selective ATR inhibitors suitable for in vitro and - most recently - in vivo studies have been identified. In this article, we will review the literature on ATR function, its role in DDR and the potential of ATR inhibition to enhance the efficacy of radiation and chemotherapy. © 2013 Elsevier Ltd.